Variable impact of Malaysia’s national language planning on non-Malay speakers in Sarawak - Ting, Su Hie (Universiti Malaysia Sarawak, UNIMAS, 2012)
The study examined the impact of the national language policy on the language use of three main ethnic groups in the Malaysian state of Sarawak. The data analyzed was based on a sociolinguistic survey on language use in six domains that involved 937 Malay, Chinese and Iban adolescents from three major towns in Sarawak. The results showed that the use of Bahasa Malaysia exceeded English usage for all three ethnic groups, showing the success of compulsory education in the national language. However, the language planning has greater impact on the Iban than on the Chinese who are shifting away from the ethnic languages of the Chinese sub-groups to Mandarin Chinese. The availability of an alternative standard language with international standing which also functions as a symbol of cultural solidarity compromises the impact of the national language policy.